Is Cronbach’s alpha relevant indicator for quality of educational measurements? (MCIT: Proceedings of International scientific and practical conference, 2023)
Mathematical model of criteria learning outcomes assessment shows that well known Cronbach’s alpha may not be appropriate indicator of assessment of professional qualifications. This indicator is good for area of learning outcomes having only one main factor. Professional standards include a list of professional functions some of them form main factor in a sense of factor analysis.
Keywords: assessment; learning outcomes; professional qualifications; Cronbach’s alpha; validity; reliability.